Network Direct Selling Organisations - Sonja Verwey; Corné Davis (Communicare)
Many studies have explored Network Direct Selling Organisations (NDSOs) because they create many communicative contexts and demonstrate such a diverse range of communicative processes that form and sustain this large industry. These organisations exist in more than 70 countries, and have almost 88 million members who generate over US$132 billion annually (WFDSA, 2011). This paper argues that although NDSOs can be differentiated from other types of organising, their characteristics can be linked to some key premises in postmodern thinking about organising. It utilises the schismatic metaphor identified by Morgan (1981) to generate further insights into the study of individuals as composite unities of operationally closed self-creating systems that cocreate organisations such as NDSOs. The schismatic metaphor is utilised to provide a powerful framework for social analysis of organisations by identifying and discussing some theoretical links between postmodernism, social autopoiesis, and second-order cybernetics.